KAJIAN ANALISIS KESESUAIAN POTENSI EKOWISATA DI OBJEK DANAU SOLE KECAMATAN AMARSEKARU KABUPATEN SERAM BAGIAN TIMUR - Supriyadi Kilbaren; Yosevita Th. Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
Lake Sole is a natural lake in East Seram Regency that has a unique nature and uniqueness in the color and taste of the water. This uniqueness makes more value on the lake when compared with the lakes in general. The uniqueness and naturalness that is owned, has not provided significant benefits to the local community and local PAD. Therefore, the purpose of this research is to know the potential of ecotourism attraction which is owned by Lake Sole, and the form of local community participation in supporting the development of ecotourism attraction product. The methods used in data collection are survey methods, interviews, and questionnaire distributions. The analysis used is quantitative descriptive analysis. The result of the research shows that Lake Sole has